Integrated Framework for Quantifying and Applying Nonworking Days to Planning and Scheduling for Determining Reasonable Construction Time - Yoon, Jongsik; Kim, Kyungrai; Choi, Byungjoo (Journal of Management in Engineering, 2022)
Determining a reasonable construction time (RCT) is crucial in project planning and schedule management. Construction projects are exposed to the external environment, including rainfall, extreme temperatures, snowfall, and high wind speed, and the RCT should be evaluated considering these risks. The risks can be reflected by activity duration using nonworking days (NWDs). However, current construction planning and scheduling practices are ineffective for dealing with of NWD characteristics because working days (WDs) and NWDs are mixed in most schedule performance data used for schedule development. Activity durations estimated using historical performance data may not appropriately reflect the activity characteristics (work type, region, and work timing), leading to an unreasonable construction time for a project. Here, we propose an activity duration segmentation method (ADSM) for determining the RCT. The ADSM can evaluate the combined effects of weather factors according to work type and determine the operation rate, which depends on start date, work type, region, and activity duration. This leads to the separation of WDs and NWDs for determining the RCT. Case-based and comparative analyses were conducted to validate the proposed method. The mean absolute percentage error (MAPE), used to validate the ADSM, was 5.79%. The results of the present study show that NWDs can be determined by considering the characteristics of the various activities (e.g., sensitivities toward environmental conditions, start date) and the environmental conditions of the project (weather conditions at the project location, working hour patterns). The ADSM suggests an integrated framework for combining activity characteristics and project environmental conditions when determining NWDs of each activity. The ADSM can be used by project owners for determining the RCT or the contract time, which varies according to activity characteristics. Also, a construction scheduler can assess to what extent the construction schedule will be influenced by NWDs.
Keywords: Activity duration; Activity duration segmentation method; Construction time; Nonworking day analyse; Project planning; Project planning scheduling; Reasonable construction time; Scheduling methods; Segmentation methods; Work type; Activity duration segmentation method (ADSM); Nonworking day analysis; Project planning scheduling; Reasonable construction time (RCT); Scheduling method